2019
DOI: 10.1073/pnas.1902250116
|View full text |Cite
|
Sign up to set email alerts
|

Two modes ofcis-activation of switch transcription by theIgHsuperenhancer

Abstract: B cell isotype switching plays an important role in modulating adaptive immune responses. It occurs in response to specific signals that often induce different isotype (I) promoters driving transcription of switch regions, located upstream of the Ig heavy chain (IgH) constant genes. The transcribed switch regions can recombine, leading to a change of the constant gene and, consequently, of antibody isotype. Switch transcription is controlled by the superenhancer 3′ regulatory region (3′RR) that establishes lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Moroever, Ig2b promoter was often activated on alleles with pre-activated Ig3. These findings strongly suggest that 3′RR activity, RNAPII, and transcription factors and co-factors are not limiting during I promoter activation and that initial activation of one promoter does not prevent activation of the other (17,112). In particular, the Ig2b promoter, which is induced by both LPS and TGF-b, was coactivated with Ig3 in the vast majority of alleles upon LPS stimulation, but was almost never co-activated with Ia after TGF-b stimulation (112).…”
Section: Compete or Not Compete For The Control Of Csrmentioning
confidence: 89%
See 2 more Smart Citations
“…Moroever, Ig2b promoter was often activated on alleles with pre-activated Ig3. These findings strongly suggest that 3′RR activity, RNAPII, and transcription factors and co-factors are not limiting during I promoter activation and that initial activation of one promoter does not prevent activation of the other (17,112). In particular, the Ig2b promoter, which is induced by both LPS and TGF-b, was coactivated with Ig3 in the vast majority of alleles upon LPS stimulation, but was almost never co-activated with Ia after TGF-b stimulation (112).…”
Section: Compete or Not Compete For The Control Of Csrmentioning
confidence: 89%
“…The single-chromosome approach also solved the longstanding issue of the polarity of the 3'RR, i.e., if the 3'RR activity was exclusively oriented toward the upstream I promoters or if it could also target a downstream promoter (17). In this regard, analysis at the single-chromosome level of activated B cells with duplicated Ia promoter downstream of the 3'RR (47) (Figure 2) revealed that the 3′RR activated both the ectopic and the endogenous Ia promoters, which points to a bidirectional activity (112).…”
Section: Compete or Not Compete For The Control Of Csrmentioning
confidence: 99%
See 1 more Smart Citation
“…the likely initial committing signal. We have recently shown that in the majority of TGFβ-activated splenic B cells, the Iγ2b and Iα promoters compete for the 3′RR 39 . Although we cannot ascertain if commitment to the Iα promoter in the original CH12 line took place following co-activation of Iγ2b and Iα or single activation of Iα, the CSR pattern in deletion clones raises the possibility that commitment to the Iα promoter has rewired the CSR machinery so that, even after deletion of Iα, it targets Iγ2b and there is optimal switching in response to the initial signal (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Super-enhancers are much more likely to act as regulators of the key processes in normal cells and pathological processes compared to conventional enhancers [ 6 ]. The IgH 3′RR super-enhancer located in the 3′-regulatory region of the IgH locus on chromosome 14 of the human genome regulates recombination in B cells (in particular, V(D)J recombination in B1 cells [ 17 ] and isotype switching, depending on the external signal in B2 cells [ 18 ]). Another element that is important in this process is the super-enhancer of the Aicda locus .…”
Section: Super-enhancers In the Regulation Of Normal And Pathological Processesmentioning
confidence: 99%